Binomial Schedule for an M/G/1 Type Queueing System with an Unreliable Server under N-Policy. (15th May 2014) - Tadj, Lotfi; Yoon, K. Paul
Abstract : We consider in this paper an M/G/1 type queueing system with the following extensions. First, the server is unreliable and is subject to random breakdowns. Second, the server also implements the well-knownN -policy. Third, instead of a Bernoulli vacation schedule, the more general notion of binomial schedule withK vacations is applied. A cost function with two decision variables is developed. A numerical example shows the effect of the system parameters on the optimal management policy.